ANALYSIS OF THE EFFECT OF THE MARKETING MIX ON THE PURCHASE DECISION OF HONEY PURCHASES AT THE ACEH AGRICULTURAL TRAINING CENTER, LEUMBAH DISTRICT, SEULAWAH, ACEH BESAR REGENCY - Khairunnisa Khairunnisa; Authar Authar; Emmia Tambarta Kembaren (Jurnal Mahasiswa Agribisnis, 2022)
Butternut squash is a type of pumpkin plant like peanut seeds and has very sweet taste of fruit flesh. This pumpkin has yellow color like butter so it is called butternut. This fruit has good nutrition for health. Butternut squash started the production at Aceh Agricultural Training Center, Saree, Leumbah Seulawah Subdistrict, Aceh Besar district since 2016. This center have 1 Ha with 5000 plants and it was became a trial area for new food commodities. The results of the honey pumpkin are sold in Farmer Agro Market Expo at the Aceh Agricultural Training Center with price of 80,000 IDR / kg. Marketing of honey pumpkin in Aceh Agricultural Training Center has several problems because the price is expensive and some people in Aceh did not know the benefits of honey pumpkin. This study aims to analyze the effect of the marketing mix on the purchasing decision of honey pumpkin at Aceh Agricultural Training Center in Leumbah Seulawah Sub-District, Aceh Besar District. The sampling method in this study used accidental sampling. Data analysis used a multiple linear regression analysis model using SPSS version 18.0 software. The results showed that the R2 coefficient value was 0.439, purchasing decisions can be explained by the four marketing mix variables, namely products, prices, places and promotions 44%. While 56% is explained by other variables outside the model. The value of F count 6.838> F table 2.640, meaning that all marketing mix variables have a significant effect on the decision to purchase honey pumpkin in Aceh Agricultural Training Center. Partially the products, prices.